2021
DOI: 10.3390/ani11061652
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Silver Nanoparticles on Proliferation and Apoptosis in Granulosa Cells of Chicken Preovulatory Follicles: An In Vitro Study

Abstract: The continuous development of poultry production related to the growing demand for eggs and chicken meat makes it necessary to use modern technologies. An answer to this demand may be the use of nanotechnology in poultry farming. One of the promising nanomaterials in this field are silver nanoparticles (AgNPs), which are used as disinfectants, reducing microbial pollution and the amounts of greenhouse gases released. This study aimed to evaluate the effect of AgNPs on the proliferation and apoptosis process in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…[ 73 ] In addition, the activity of caspase‐3 correlated positively with the size of Ag NPs. [ 74 ] Caspase‐9 is an initial caspase that recruits and activates caspase‐3, thereby initiating the caspase cascade reaction and inducing the apoptosis of target cells. Several recent reports have shown that apoptosis induced by ZnO NP exposure was closely related to the activation of caspase‐3, caspase‐7, and caspase‐9.…”
Section: Cytotoxicity Mechanism Of Metal‐based Npsmentioning
confidence: 99%
“…[ 73 ] In addition, the activity of caspase‐3 correlated positively with the size of Ag NPs. [ 74 ] Caspase‐9 is an initial caspase that recruits and activates caspase‐3, thereby initiating the caspase cascade reaction and inducing the apoptosis of target cells. Several recent reports have shown that apoptosis induced by ZnO NP exposure was closely related to the activation of caspase‐3, caspase‐7, and caspase‐9.…”
Section: Cytotoxicity Mechanism Of Metal‐based Npsmentioning
confidence: 99%
“…In several studies, Ag-and CuO-NPs were shown to influence proliferation in different cell types (Rodríguez-Razón et al 2018;Shafagh et al 2015). Smaller Ag-NPs were more toxic than larger NPs, in spite of the fact that smaller NPs tended to aggregate during cell uptake, which limited binding to cell membranes (Katarzynska-Banasik et al 2021). In our study, at 24 h, 48 h, and 72 h, Ag-NPs, regardless of size, inhibited cell proliferation when compared with untreated cells (Fig.…”
Section: Discussionmentioning
confidence: 99%